Screening and characterization of alpha-amylase expressing gene from amylolytic bacteria isolated from Sago humus - Rohanie, Binti Bohan. (Universiti Malaysia Sarawak (UNIMAS), 2006)
The amylolytic bacterial colony that yields high level of the a-amylase enzyme activity by producing the biggest halo when flooded with Lugol's Iodine into minimal starch media was isolated from sago humus. Result from the biochemical tests show that these bacteria pertain in genus of gram-positive Bacillus spp. However, the molecular identification of the isolated bacteria by direct sequencing of 16S rRNA purified PCR products was unsuccessful. In order to isolate a-amylase gene from the isolated bacteria, Polymerase Chain Reaction (PCR) technique using two different set of specific primers namely ApAl&ApA2 and AmBcl&AmBc2 primers was done. Approximately 500bp and 750bp a-amylase gene were successfully isolated respectively using both sets of primers which then purified and sent for direct sequencing. These PCR products were also cloned into pGEM-T Easy vector system (Promega) in Escherichia coli XL-I Blue competent cells for propagation of the products. The white colonies were then screened for insert using colony PCR and Restriction Endonuclease analysis.